Numerical simulation of skin formation: epidermal stem cells and undulation of the basal layer. Issue 1 (May 2021) - Oba, Shu; Nagayama, Katsuya
Abstract: The basal layer at the base of the epidermis produces new epidermal cells once a week and plays an important role in skin formation. Interestingly, the basal layer undulates, and the amplitude of this undulation is dependent on age or disease. However, the mechanisms driving this phenomenon have not been well studied. This work simulated the skin formation process using an original method to understand the mechanism of the undulation formation in the basal layer. The basal layer has cells with both short and long cell cycles, but only the former has been examined in previous studies. Accordingly, we more accurately simulated the skin formation process by including cells with a long cell cycle and observed undulation of the basal layer. Based on our findings, we propose that the basal layer undulates due to the interaction between two types of basal layer cells.